Verbiage and empathy. On Memory by Correspondence by Emma Reyes - Uribe Botero, Ángela (Estudios de Filosofía, 2016)
The purpose of this paper is to deepen into the sense of isolation in a convent in which Emma Reyes, the author of the book Memoria por correspondencia was forced to live. Taking account of Maxine Sheets- Johnstone's term ''immortality ideologies'', in the first part of the paper I try to disclose what I see as the origin of that isolation. In the second part, I weave a relation between the way the immortality ideology is instantiated in that convent and the term ''empathy'', as used in phenomenology. I conclude showing how empathy can be impoverished as to the point where the particularities of an other's experiences are perceived only in a marginal and peripheral way.